Bladder-sparing therapy in a case report of huge muscle-invasive bladder IMT treated with 1470 nm diode laser en bloc resection followed by laparoscopic partial cystectomy - Chu, Junhao; Yuan, Huisheng; Zhang, Zhihui; Kan, Jiajun; Duan, Shishuai; Wang, Zilong; Wang, Muwen (Frontiers in Oncology, 2025)
BackgroundBladder inflammatory myofibroblastic tumor (IMT) is a rare intermediate malignancy. Muscle-invasive bladder IMT is associated with a high risk of recurrence and metastasis, and bladder-sparing treatments for this condition are still under exploration. This case aims to evaluate the therapeutic efficacy of 1470 nm diode laser transurethral en bloc resection (ERBT) followed by laparoscopic partial cystectomy in the treatment of muscle-invasive bladder IMT.Methods and resultsA 23-year-old male patient presented with painless terminal gross hematuria and was treated at Shandong Provincial Hospital of Shandong First Medical University. Computed tomography urography (CTU) and magnetic resonance imaging (MRI) identified a large tumor on the anterior bladder wall with muscle layer invasion, measuring approximately 5.0 × 3.9 × 4.3 cm. The patient underwent 1470 nm laser ERBT, followed by laparoscopic partial cystectomy 35 days later. Pathological examination following 1470 nm laser resection confirmed the diagnosis of an IMT with malignant potential, showing anaplastic lymphoma kinase (ALK) positivity, a Ki-67 index of 20% in hotspot regions, and ALK gene rearrangement detected by fluorescence in situ hybridization (FISH). Pathology after the secondary laparoscopic partial cystectomy showed tumor invasion into the superficial muscle layer, with negative margins at the resection site. MRI and cystoscopy showed no recurrence during 1 year follow-up.ConclusionThis case presents a patient with a huge muscle-invasive bladder IMT who received bladder-sparing therapy through 1470 nm diode laser ERBT followed by laparoscopic partial cystectomy. During subsequent follow-ups, the patient showed good recovery with no signs of recurrence, providing a promising treatment concept for bladder-sparing therapy in muscle-invasive bladder IMT.